Morphological and bioecological features and reproduction of Oriental persimmon (Diospyros lotusL.) in the Forest-Steppe Zone of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Morphological andbioecological featuresof Oriental persimmon (Diospyros lotusL.)in the Forest-Steppe zone of Ukraine are elucidated. Reproductive ability, morphological and metrical characteristics of vegetative and generative organs are studied. The methods and terms of propagation are described.
Keywords: Oriental persimmon (Diospyros lotus L.), morphology,bioecology,reproductive ability, Forest-Steppe zone of Ukraine.